Religion influence on end-of-life decisions - Paulino, Carolina (Portuguese Journal Internal Medicine, 2014)
End-of-life decisions (ELD) includes medical options of whether or not to resuscitate, to withdrawing or withholding from life support treatment. These concepts have emerged over the past three decades in an attempt to prevent the institution of therapies that do not provide any additional improvement of patient´s life except just prolonging it. Globalization has enabled an associated gradual increase with interactions amongst various religions. These religions share different beliefs and points of views regarding the involvement of doctors, patients and the family in ELD and the ethics involved when facing death. The clarification of patient´s religious beliefs can lead to a better communication between the doctor, the patient and their families and enabling thus a more consistent decision making regarding end-of-life care.